ANALISIS PEMENUHAN LEMBAGA PENDIDIKAN SEKOLAH DASAR DI DISTRIK MIMIKA BARU KABUPATEN MIMIKA - Setrianus .; Nely Salu Padang (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2017)
The aim this studyto analyze the ratio of the fulfillment of the Elementary School Education Institution in the Mimika Baru District of Mimika Regency. Data collection tool used in the research is to conduct interviews and direct observation to get the ratio of needs and fulfillment of Primary School. The result of this research shows that the requirement of the elementary school education institution is in accordance with the number of elementary school children in Mimika Baru District of Mimika Regency, which are 50 elementary schools which are available with the number of primary school children as many as 27,263 children, but the problem is the deployment and capacity not evenly distributed